Global and Domestic Status and Prospects of Green Biomass Utilization - Antal, Gabriella (International Journal of Engineering and Management Sciences, 2018)
Nowadays, the energy consumption of global population is depending on fossil fuels, but the role of renewable energies has been increasing rapidly, primarily due to the depletion of fossil fuels, the appreciation of environmental problems and climate policies. Biomass is the fourth most important energy resource in the world, provided an estimated 70% of global renewable energy supply. However, the annual growth rate of biomass is lagging behind modern renewable energy sources. The type of biomass is very diverse and can be processed and utilised by different methods. Currently, in the "green chemistry" industry (the replacement of petroleum-based, synthetic chemical raw materials with bio-based compounds from plant biomass), the importance of combustion, pyrolysis, biogas, bioethanol, biodiesel and basic chemical compounds production have been increasing. The objectives of the present research is to analyse the global and domestic status of renewable energies and biomass production, furthermore the possibilities of utilization of perennial, herbaceous biomass plant, the giant reed (Arundo donax L.), with which has been conducting research for numerous years at the University of Debrecen.